How everyday life matters: everyday politics, everyday consumption and social change. Issue 1 (11th August 2022) - Yates, Luke
Abstract : Everyday life, a nebulous and contested concept, is increasingly featuring in accounts of socioeconomic transformation. This article reviews its connections with consumption, sometimes referred to as 'everyday consumption'; and to political action, 'everyday politics'. It brings together different theoretical and empirical agendas to explore intersections and shifts in ideas around transformation. The first section describes the ways in which everyday life has become associated with consumption, especially through studying practices and their relationship with ecological change. It argues that power, politics and resources are largely absent from these discussions. The second section therefore reviews literature on power, noting that influential theory, including feminist perspectives, practice theory and the work of Michel Foucault, all places emphasis on quotidian situations, interactions and instances, offering ways forward to addressing the absence of power in research on everyday consumption. The third section explores and compares the diverse literature on 'everyday politics', lifestyle movements, everyday resistance, prefiguration, life politics and subpolitics. The article groups these and other claims about how the everyday matters for social change into a set of common debates around resources, issues and themes, objects of study, and consequences . This helps identify some notable empirical findings, contrasting analytical claims, and suggests some priorities for future research.